Intensitas Bermain Game Online dan Empati pada Remaja - Dwibowo, Septyanto; Satyaka, Ahmad Raif; Sulistyaningsih, Wiwik (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Playing online games is a common activity among adolescents in Indonesia as a form of entertainment, and it often becomes an influence on the development of empathy, especially in teenagers. This research aims to determine whether there is a difference in empathy among adolescents based on the intensity of online gaming. The game genre studied is MOBA (Multiplayer Online Battle Arena), which is played by 10 people, with each team consisting of 5 players. One match is estimated to last between 10-30 minutes or longer, and the objective is to destroy the opposing team's base. This game requires a high level of teamwork and social interaction among team members. The study uses the Basic Empathy Scale (BES) as a tool to measure empathy, which assesses two components of empathy: affective and cognitive. To measure the intensity of online gaming, the researchers collected data on the average amount of time spent playing online games per week. There were 108 respondents in this study, aged 15-18 years, who played MOBA games and resided in Jabodetabek. Using the ANOVA analysis method, the results showed a significant difference in empathy based on the intensity of online gaming, with a significance value of 0.027 (p-value <0.05). Significant differences in empathy were found between adolescents with moderate and high levels of online gaming intensity (p-value 0.02 <0.05). However, there was no significant difference between the low and moderate groups (p-value 0.547 >0.05), nor between the high and low groups (p-value 0.054 >0.05). Adolescents with high gaming intensity tend to have higher levels of empathy. In the context of MOBA games, which are typically played with friends and require intensive social interaction, it can be concluded that games with high social interaction (in this study, the MOBA genre) are associated with higher empathy. These findings align with other studies that have found that social interaction in games can enhance empathy.